2022
DOI: 10.1002/mame.202200615
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Dynamic Behavior of Condensation‐Cured Silicone Elastomers Caused by a Catalyst

Abstract: This study demonstrates that dibutyltin‐dilaurate (DBTL), commonly used to catalyze condensation‐cured silicone elastomers, causes dynamic behavior in the silicone network, which is attributed to the catalyst finding a way to become part of the elastomer network. Furthermore, it establishes that by choosing an appropriate silanol‐terminated polydimethylsiloxane (HO‐PDMS‐OH) chain length, the catalyst causes the gelation of the system without a cross‐linker. To the best of authors' knowledge, this is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The silanolate groups can then exchange with siloxanes in a substitution-like reaction. These approaches have proved useful in both elastomers and thermosets. , Recently, there has been work on direct silyl ether metathesis using catalysts, Bronsted or Lewis acids, or the introduction of free hydroxyls into the network. , Du Prez and co-workers have developed siloxane-containing vitrimers with very fast dynamics (below 10 s) in the presence of basic catalysts. , Due to the flexibility of the siloxane units, the prepared resins exhibited low viscosities, which offers significant advantages for fiber-reinforced polymer composite manufacturing. Additionally, it has been shown that the incorporation of siloxane groups into reprocessable networks improves the dielectric properties and ductility. , …”
mentioning
confidence: 99%
“…The silanolate groups can then exchange with siloxanes in a substitution-like reaction. These approaches have proved useful in both elastomers and thermosets. , Recently, there has been work on direct silyl ether metathesis using catalysts, Bronsted or Lewis acids, or the introduction of free hydroxyls into the network. , Du Prez and co-workers have developed siloxane-containing vitrimers with very fast dynamics (below 10 s) in the presence of basic catalysts. , Due to the flexibility of the siloxane units, the prepared resins exhibited low viscosities, which offers significant advantages for fiber-reinforced polymer composite manufacturing. Additionally, it has been shown that the incorporation of siloxane groups into reprocessable networks improves the dielectric properties and ductility. , …”
mentioning
confidence: 99%